Research on Library Bibliotherapy Services for Addressing Inferiority Complex Among Economically Disadvantaged Students in Western Chinese Universities (Journal of research in medical and health sciences, 2025)
This paper addresses the issue of inferiority complex among economically disadvantaged students in Western Chinese universities, exploring intervention strategies and practical pathways for library bibliotherapy services. By analyzing the characteristics and causes of this inferiority complex, and integrating the theoretical foundations and mechanisms of bibliotherapy, a library bibliotherapy service framework based on the three dimensions of "Needs—Resources—Assessment" is designed. Corresponding implementation safeguards are also proposed, aiming to provide references for constructing an effective psychological support system within Western Chinese university libraries.
Keywords: Western chinese universities; Economically disadvantaged students; Inferiority complex; Bibliotherapy; Library services